A New Hypothesis of the Phylogenetic Relationships of the Tylosaurinae (Squamata: Mosasauroidea) - Jiménez-Huidobro, Paulina; Caldwell, Michael W. (Frontiers in Earth Science, 2019)
Tylosaurinae Williston, 1897, is reconstructed in most analyses as the sister group of the Plioplatecarpinae Dollo, 1884. The most distinctive characteristic of the group is an elongate edentulous rostrum on the premaxilla. Members of the tylosaurine subfamily are divided into two genera: Tylosaurus Marsh, 1872, and Taniwhasaurus Hector, 1874. When all arguably valid tylosaurine species are included in a single phylogenetic analysis, some clades are well supported, i.e., the clade formed by T. proriger (Cope, 1869) + T. bernardi (Dollo, 1885), or the clade T. pembinensis (Nicholls, 1988) + T. saskatchewanensis. In contrast, clade relationships for other species are unresolved, i.e., T. gaudryi (Thevenin, 1896), T. nepaeolicus (Cope, 1874), and the several species within the genus Taniwhasaurus. When T. gaudryi (Thévenin, 1896), Ta. ‘mikasaensis’ Caldwell et al., 2008, and ‘T’. capensis ' Broom, 1912 were removed from the analysis, T. nepaeolicus appeared as the basal member of the genus. The relationships within the genus Taniwhasaurus are unresolved; however, when the problematic taxa are removed, the genus is monophyletic, with Ta. oweni as the sister group of Ta. antarcticus. Based on morphological characters present in the holotype of ‘T’. capensis Broom, 1912, we suggest a re-assignation to the genus Taniwhasaurus, based on the flutes and facets in the crown of the two preserved replacement teeth. The lack of a clear diagnosis of Hainosaurus/Tylosaurus neumilleri leaves this taxon as nomen dubium; the few characters visible on the specimen show strong similarities to both T. pembinensis and T. saskatchewanensis; therefore the specimen cannot be identified beyond Tylosaurus sp. Reassessment of the known materials of the Japanese species Ta. ‘mikasaensis’ suggests that the various specimens do not display sufficient diagnostic characters to support ‘mikasaensis’ as distinct from Taniwhasaurus oweni. The hypothesis for a North Atlantic Circle Basin distribution for species of the genus Tylosaurus from the Coniacian to the Maatrichtian is supported, and a more cosmopolitan distribution is suggested for the genus Taniwhasaurus (Santonian to Maastrichtian) with species present along the margins of the Pacific, Indian and Antarctic Ocean Basins.